2020
DOI: 10.1186/s12879-020-05540-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical, para-clinical and laboratory findings in survived and deceased patients with COVID-19: diagnostic role of inflammatory indications in determining the severity of illness

Abstract: Background Since December 2019, when a cluster of pneumonia cases due to SARS-CoV-2 initially emerged in Wuhan city and then rapidly spread throughout the world, the necessity for data concerning the clinical and para-clinical features of Iranian patients with COVID-19 was highlighted. Therefore, we aimed to compare the clinical, para-clinical and laboratory evidences of deceased patients with survival group. Methods We extracted data regarding 233 patients with laboratory-confirmed COVID-19 from Buali Hospit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 35 publications
5
34
1
1
Order By: Relevance
“…This hyperresponsiveness was also found in other studies [ 224 ]. Some clinical studies report that thrombocytopenia is associated with increased mortality [ 4 , 5 ], whereas other do not [ 215 , 225 ]. This discrepancy might depend on disease severity, comorbidities or the type of care provided.…”
Section: Resultsmentioning
confidence: 99%
“…This hyperresponsiveness was also found in other studies [ 224 ]. Some clinical studies report that thrombocytopenia is associated with increased mortality [ 4 , 5 ], whereas other do not [ 215 , 225 ]. This discrepancy might depend on disease severity, comorbidities or the type of care provided.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, two studies including small cohorts have been published exploring the usefulness of known hemogram-derived ratios. One describes laboratory and radiological findings in a small group of patients 21 and another compares blood inflammatory markers in SARS-CoV-2 virus infection to influenza A. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Another immune dysregulated feature is the remarkable increase in neutrophil-to-lymphocyte ratio (NLR) [8,32], which usually depicts a higher disease severity and poor clinical outcome [33]. NLR may also work as an independent prognostic marker to predict COVID-19 disease severity [34]. In a retrospective study of the 55 COVID-19 patients, transcriptional profiling of the immune cells revealed excessive neutrophils count and the associated NET.…”
Section: Changes Of Immune Cellsmentioning
confidence: 99%